The validation of extended software process assessment and certification model using focus group - Mohamed, Shafinah Farvin Packeer; Baharom, Fauziah; Deraman, Aziz; Yusof, Yuhanis (2016)
The Extended Software Process Assessment and Certification (ESPAC) Model is a model that assesses and certifies the effectiveness and efficiency of software process, which focuses on the agile and secure software processes.The model was validated by assessing and certifying a real project from the software industry through focus group discussion. This paper discusses the execution of the validation as well as the results for the assessment and certification exercise performed on the project.Outcomes from the assessment and certification results show that the project has been implemented systematically; however, there exist some practices with low performance. Accordingly, improvements can be made by the software practitioners on the software practices which achieve low scores. Consequently, it indicates that the ESPAC Model is not only suitable for assessing and certifying software process, but can also be used for continuous improvement.